Mpox Neutralizing Antibody Response to LC16m8 Vaccine in Healthy Adults - Morino, Eriko; Mine, Sohtaro; Tomita, Noriko; Uemura, Yukari; Shimizu, Yosuke; Saito, Sho; Suzuki, Tetsuya; Okumura, Nobumasa; Iwasaki, Haruka; Terada, Junko; Ainai, Akira; Sakai, Yusuke; et al. (NEJM evidence, 2024)
BACKGROUND: Vaccination against mpox (formerly known as monkeypox), an infectious disease caused by the monkeypox virus (MPXV), is needed to prevent outbreaks and consequent public health concerns. The LC16m8 vaccine, a dried cell-cultured proliferative live attenuated vaccinia virus–based vaccine, was approved in Japan against smallpox and mpox. However, its immunogenicity and efficacy against MPXV have not been fully assessed. We assessed the safety and immunogenicity of LC16m8 against MPXV in healthy adults. METHODS: We conducted a single-arm study that included 50 participants who were followed up for 168 days postvaccination. The primary end point was the neutralizing antibody seroconversion rate against MPXVs, including the Zr599 and Liberia strains, on day 28. The secondary end points included the vaccine “take” (major cutaneous reaction) rate, neutralizing titer kinetics against MPXV and vaccinia virus (LC16m8) strains, and safety outcomes. RESULTS: Seroconversion rates on day 28 were 72% (36 of 50), 70% (35 of 50), and 88% (44 of 50) against the Zr599 strain, the Liberia strain, and LC16m8, respectively. On day 168, seroconversion rates decreased to 30% (15 of 50) against the Zr599 and Liberia strains and to 76% (38 of 50) against LC16m8. The vaccine “take” (broad definition) rate on day 14 was 94% (46 of 49). Adverse events (AEs), including common solicited cutaneous reactions, occurred in 98% (45 of 48) of participants; grade 3 severity AEs occurred in 16% (8 of 50). No deaths, serious AEs, or mpox onset incidences were observed up to day 168. CONCLUSIONS: The LC16m8 vaccine generated neutralizing antibody responses against MPXV in healthy adults. No serious safety concerns occurred with LC16m8 use. (Funded by the Ministry of Health, Labour and Welfare of Japan; Japan Registry of Clinical Trials number, jRCTs031220171.)